Study of Losses in the Production Line of a Large Footwear Company - Alencar, Marcelo Sampaio de (Revista de Economia, 2020)
The article analyzes the production loss, also referred to as reject, in the largest footwear producer of the World, the Alpargatas company. The article presents a discussion of the probabilistic modelling, the development of a stochastic model, that uses Itô stochastic integration, based on temporal series provided by the company, and the identification of eventual solutions to the loss of production.